ASSOCIATION OF THROMBOCYTOPENIA, ACTIVATED PARTIAL THROMBOPLASTIN TIME WITH BLEEDING MANIFESTATION IN DENGUE PATIENTS - Dr Suman G R; Dr Hoysala Kumar D P; Dr Bharath S J (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Dengue virus infection can lead to severe complications, including bleeding, due to alterations in coagulation pathways. One of the key laboratory tests used to assess coagulation status is the activated partial thromboplastin time (aPTT), which measures the time it takes for blood to clot. In dengue, coagulopathy, including thrombocytopenia and endothelial dysfunction, can result in prolonged aPTT, serving as a potential early indicator of bleeding risk. A prolonged aPTT, especially when combined with low platelet counts and other clinical signs of hemorrhage, can predict the onset of severe conditions such as dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). Monitoring aPTT levels in dengue patients allows for the early identification of coagulopathy, enabling clinicians to take proactive measures, such as platelet transfusion and more intensive management, to prevent life-threatening bleeding episodes. This abstract highlights the significance of aPTT as an early predictor of bleeding in dengue virus infection, underscoring its role in guiding clinical decisions and improving patient outcomes in severe cases.